Legislative and application techniques in labour measures at COVID 19 in Spain - Cruz Villalón, Jesús (2020)
The declaration of the state of alarm by the Spanish Government in March 2020, which has confined the population to their homes, with very intense effects of paralyzing business activity, has had a very notable impact in the field of work, with very relevant measures, with a strong impact on both the labour market and labour legislation. Among the most important measures are the following: (1) rules of preference for distance working for those companies that were forced to close their work centres and, as far as possible, avoid the destruction of these jobs; (2) establishment of a system of suspension of employment contracts due to force majeure, favourable to both companies and workers, which would also avoid the adoption of mass redundancies; (3) declaration of the unjustified nature of redundancies that were intended to be motivated by the cessation of productive activity due to the health crisis; (4) formulas favouring the conciliation of family and work responsibilities during the development of the measures against the pandemic; (5) exceptional formula of recoverable paid leave; (6) economic measures to attend to workers without work activity through Social Security benefits; (7) introduction of a new Social Security benefit as Minimum Life Income.The present study, leaving aside the significance and scope of the measures adopted in this context, aims to analyze the process of elaboration of these emergency regulations, the intervention of the various public powers both in the process of approval and application, as well as the marginal role of social consensus, collective bargaining and the participation of workers in the company. In this way, the specialties of the measures are addressed from the perspective of the game of the rules related to Sources of Law, as well as the role played by the habitual protagonists in the development of our system of labour relations.